TGF-β Signaling in Neuronal Stem Cells. Issue 4 (2008) - Yun, Chohee; Mendelson, Jonathan; Blake, Tiffany; Mishra, Lopa; Mishra, Bibhuti
Abstract : Transforming growth factor beta (TGF- β ) signaling has diverse and complex roles in various biological phenomena such as cell growth, differentiation, embryogenesis and morphogenesis. ES cells provide an essential model for understanding the role of TGF- β signaling in lineage specification and differentiation. Recent studies have suggested significant role of TGF- β in stem/progenitor cell biology. Here in this review, we focus on the role of the TGF- β superfamily in neuronal development.